2002
DOI: 10.3354/dao050095
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of gill-associated virus (GAV) in the black tiger prawn Penaeus monodon

Abstract: Chronic gill-associated virus (GAV) infection is endemic in Penaeus monodon broodstock captured from north-east Queensland in Australia and in farmed shrimp produced from these. We investigated the role of vertical transmission in perpetuating the high prevalence of these chronic GAV infections. Reverse transcription (RT)-nested PCR detected GAV in spermatophores and mature ovarian tissue from broodstock and in fertilized eggs and nauplii spawned from wild-fertilized females. In laboratory-reared P. monodon (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 16 publications
3
36
0
Order By: Relevance
“…This systemic distribution of virus is characteristic of an acute infection stage, and supports previous reports of GAV tissue distribution determined by in situ hybridisation (Tang et al 2002, Spann et al 2003. The high initial GAV levels found in this study for spermatophores supports previous observations with endpoint RT-PCR (Walker et al 2001, Cowley et al 2002a, Spann et al 2003.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This systemic distribution of virus is characteristic of an acute infection stage, and supports previous reports of GAV tissue distribution determined by in situ hybridisation (Tang et al 2002, Spann et al 2003. The high initial GAV levels found in this study for spermatophores supports previous observations with endpoint RT-PCR (Walker et al 2001, Cowley et al 2002a, Spann et al 2003.…”
Section: Discussionsupporting
confidence: 81%
“…Recent surveys revealed that the prevalence of chronic GAV infection approaches 100% in wild and farmed Penaeus monodon along the east coast of Australia (Cowley et al 2002a, Walker et al 2001. Whereas conventional detection systems indicate whether GAV is present or absent in prawns, they only give a crude estimation of the abundance of GAV, which provides farmers with little information on the health status of their cultured stocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no published studies that evaluate the possibility of vertical transmission of ranavirus. However, there are reports of other DNA viruses, such as gill associated virus and channel catfish virus, that have demonstrated vertical transmission of virus from adults to eggs (Wise et al 1988, Brauer 1995, Cowley et al 2002. It is possible that vertical transmission is occurring in anurans infected with ranavirus based on data collected from this research.…”
Section: Discussionmentioning
confidence: 86%
“…GAV is also endemic and occurs commonly in this population of P. monodon (Spann et al 1995, Cowley et al 2000a, Walker et al 2001, which is the primary source of broodstock used to supply hatcheries in Queensland. It has been suggested that GAV may be maintained in this population by vertical transmission (Cowley et al 2002). It will be important to determine whether MoV is also transmitted vertically and if so, the mechanisms by which this occurs.…”
Section: Discussionmentioning
confidence: 99%